Romantic Misfits - Miles, R. author. aut Link
XVIII, 227 p.
Keywords: This book explores the false starts and disturbances of Romantic writing in Britain - 'misfits' and misfittings - as both a constitutive challenge to canonical romanticism and a distinctive literary field worth examining on its own account. Misfits include the Shakespeare forger W.H. Ireland, the novel itself, and the culture of Dissent.